Sequential Immunization With Heterologous Viruses Does Not Result in Attrition of the B Cell Memory in Rainbow Trout - Navelsaker, Sofie; Magadan, Susana; Jouneau, Luc; Quillet, Edwige; Olesen, Niels J.; Munang'andu, Hetron Mweemba; Boudinot, Pierre; Evensen, Øystein (Frontiers in Immunology, 2019)
Long-term immunity is of great importance for protection against pathogens and has been extensively studied in mammals. Successive heterologous infections can affect the maintenance of immune memory, inducing attrition of T memory cells and diminishing B cell mediated protection. In fish, the basis of immune memory and the mechanisms of immunization to heterologous pathogens remain poorly understood. We sequentially immunized isogenic rainbow trout with two immunologically distinct viruses, VHSV and IPNV, either with one virus only or in combination, and analysed the antibody responses and repertoires. Neutralizing antibodies and ELISPOT did not reveal an effect of heterologous immunization. Using a consensus read sequencing approach that incorporates unique barcodes to each cDNA molecule, we focused on the diversity expressed by selected responding VH/C combinations. We identified both public and private responses against VHSV and/or IPNV in all groups of fish. In fish immunized with two viruses, we registered no significant reduction in the persistence of the response towards the primary immunization. Similarly, the response to the second immunization was not affected by a prior vaccination to the other virus. Our data suggest that heterologous immunization does not enforce attrition of pre-existing antibody producing cells, which may impair the protection afforded by multiple successive vaccinations. These observations are potentially important to improve vaccination strategies practiced in aquaculture.